Linking microhabitat selection, range size, reproductive state, and behavioral state in greater sage‐grouse. (1st June 2022) - Gelling, Erin L.; Pratt, Aaron C.; Beck, Jeffrey L.
Abstract: A female's reproductive status influences her behavior which affects habitat selection and range size; however, reproduction and behavior are generally unaccounted for in habitat selection studies. Range size, daily activity, and habitat selection between reproductive states have rarely been investigated in a connected manner. We focused on brood‐rearing and broodless (i.e., females without young) greater sage‐grouse ( Centrocercus urophasianus ). Our objectives were as follows: 1) identify differences between reproductive state (females with broods 0–2 weeks, broods 3–5 weeks, and broodless females) and behavioral state (foraging, day roosting, and night roosting) in microhabitat selection, 2) evaluate daily activity for brood‐rearing and broodless females, and 3) contrast daily and seasonal range sizes for each reproductive state. We collected Global Positioning System location and accelerometer data every 5 min from female sage‐grouse in Carbon County, Montana, and Park County, Wyoming, USA, in 2018–2019. We sampled microhabitat for 36 females at 276 bird‐use and random plots, estimated ranges for 38 females, and measured activity for 43 females. Females with broods 0–2 weeks selected against visual obstruction and for perennial grasses at night roosts, females with broods 3–5 weeks selected for visual obstruction when foraging and against visual obstruction and annual grasses but for sagebrush cover at night roosts; however, broodless females showed no selection. Patterns of daily activity differed between females with broods 0–2 weeks and broodless females; females with broods 3–5 weeks showed an intermediate pattern. Females with broods 0–2 weeks had the smallest daily (0.027 km 2 ) and seasonal (0.21 km 2 ) ranges compared with females with broods 3 – 5 weeks (daily = 0.038 km 2, seasonal = 0.36 km 2 ) and broodless females (daily = 0.035 km 2, seasonal = 0.44 km 2 ). Our results indicated the importance of considering reproductive and behavioral state and accounting for habitats and space required by all individuals in conservation and management decisions. Abstract : We investigated and found differences between behavioral states in habitat selection and differences between reproductive states in habitat selection, daily and seasonal range size, and daily activity for greater sage‐grouse ( Centrocercus urophasianus ). Our results indicate the importance of considering reproductive and behavioral state in habitat selection studies and accounting for habitats and space required by all individuals in conservation and management decisions.